Two new species of Aristolochia series Thyrsicae (Aristolochiaceae) from southern Central America, with comments on morphologically similar species - Jiménez Vargas, José Esteban (2021)
Aristolochia longissima and Aristolochia ornithorhyncha, two new species from the lowland moist forest from the Pacific watershed of southern Costa Rica and western Panama, are described and illustrated. Both species can be distinguished from most other species of Aristolochia series Thyrsicae, because of their leaves with pellucid gland dots, which are here documented in Aristolochiaceae for the first time. Comments about their distribution, habitat, phenology, conservation status and distinction from related species are provided. The circumscription of Aristolochia belizensis, A. chapmaniana, A. fragrantissima, A. ovalifolia, A. schmidtiana and A. tonduzii is discussed.